Non-invasive coronary imaging in patients with COVID-19: A narrative review. Issue 149 (April 2022) - Onnis, Carlotta; Muscogiuri, Giuseppe; Paolo Bassareo, Pier; Cau, Riccardo; Mannelli, Lorenzo; Cadeddu, Christian; Suri, Jasjit S.; Cerrone, Giulia; Gerosa, Clara; Sironi, Sandro; Faa, Gavino; Carriero, Alessandro; et al.
Highlights: Coronary CT Angiography (CCTA) represents a rapid non-invasive imaging technique for cardiovascular risk evaluation in patients during and after exposure to SARS-CoV-2. CCTA with a 'quadruple rule out' protocol can identify pneumonia, pulmonary embolism, CAD and myocardial injury in acute chest pain. CCTA has high accuracy and high negative predictive value, enabling identification of acute coronary syndromes without ST-segment elevation (NSTE-ACS) for which invasive testing will be futile. Coronary artery calcification (CAC) seems a promising tool to evaluate CAD risks in COVID-19 patients. CCTA has the potential to identify the phenotype of vulnerable plaques at higher risk of rupture and may be used to select patients at very-high risk for adequate invasive imaging. Perivascular adipose tissue (PVAT) evaluated with CCTA may provide comprehensive information on inflammation grade and has the potential to provide predictive markers for pneumonia, in-hospital mortality and ICU admission. Artificial intelligence (AI) and deep learning (DL) algorithms provide tools to reduce post-processing time and increase diagnostic accuracy. Abstract: SARS-CoV-2 infection, responsible for COVID-19 outbreak, can cause cardiac complications, worsening outcome and prognosis. In particular, it can exacerbate any underlying cardiovascular condition, leading to atherosclerosis and increased plaque vulnerability, which may cause acute coronary syndrome. We review current knowledge on the mechanisms by which SARS-CoV-2 can trigger endothelial/myocardial damage and cause plaque formation, instability and deterioration. The aim of this review is to evaluate current non-invasive diagnostic techniques for coronary arteries evaluation in COVID-19 patients, such as coronary CT angiography and atherosclerotic plaque imaging, and their clinical implications. We also discuss the role of artificial intelligence, deep learning and radiomics in the context of coronary imaging in COVID-19 patients.